Herpes Simplex Virus Latency: The DNA Repair-Centered Pathway - Jay C. Brown (Advances in Virology)
Like all herpesviruses, herpes simplex virus 1 (HSV1) is able to produce lytic or latent infections depending on the host cell type. Lytic infections occur in a broad range of cells while latency is highly specific for neurons. Although latency suggests itself as an attractive target for novel anti-HSV1 therapies, progress in their development has been slowed due in part to a lack of agreement about the basic biochemical mechanisms involved. Among the possibilities being considered is a pathway in which DNA repair mechanisms play a central role. Repair is suggested to be involved in both HSV1 entry into latency and reactivation from it. Here I describe the basic features of the DNA repair-centered pathway and discuss some of the experimental evidence supporting it. The pathway is particularly attractive because it is able to account for important features of the latent response, including the specificity for neurons, the specificity for neurons of the peripheral compared to the central nervous system, the high rate of genetic recombination in HSV1-infected cells, and the genetic identity of infecting and reactivated virus.